FAKTOR–FAKTOR PEMILIHAN PENGGUNAAN JENIS ALAT KONTRASEPSI KELUARGA MISKIN DI KELURAHAN KELAYAN TIMUR KECAMATAN BANJARMASIN SELATAN - Nana Elidasari; Sidharta Adyatma; Deasy Arisanty (JPG (Jurnal Pendidikan Geografi), 2016)
The research titled “The Factors of  Chosen Contraseption Stuff Usage by Poor Family in East Kelayan Village, South Borneo Regency”. The purpose of this research is to knowing the factors of chosen contraseption stuff usage by poor family.The populations in this research are fertiled couple (PUS) activated members who living at East Kelayan village. The biggest sample are 335 members as respondents. The technique used is simple random sampling. The data that used are primary data and secondary data. The primary data got directly on the field using questioners and secondary data got from government instancy such as BPS, BKKBN and Kantor Dinas Sosial & Tenaga Kerja. Analyze technique used is percentation analysis and class interval.The results of this research shown are couples factor is the high class with 100%, where as the lowest class with 0% therefor the respondents are choosing the contraseption their have using. Health factor is the high class with 88%, where as the lowest class with 12%  therefor the respondents are choosing the contraseption their have using. Stuff and metodes of contraseption is the high class with 16%, where as the lowest class with 84% therefor the respondents are choosing the contraseption their have usingKeywords : Contraseption Stuff, Poor Family